Conflict and Agency among Sex Workers and Pimps: A Closer Look at Domestic Minor Sex Trafficking. Issue 1 (May 2014) - Marcus, Anthony; Horning, Amber; Curtis, Ric; Sanson, Jo; Thompson, Efram
The dominant understanding in the United States of the relationship between pimps and minors involved in commercial sex is that it is one of "child sex trafficking, " in which pimps lure girls into prostitution, then control, exploit, and brutalize them. Such narratives of oppression typically depend on postarrest testimonials by former prostitutes and pimps in punishment and rescue institutions. In contrast, this article presents data collected from active pimps, underage prostitutes, and young adult sex workers to demonstrate the complexity of pimp-prostitute dyads and interrogate conventional stereotypes about teenage prostitution. A holistic understanding of the factors that push minors into sex work and keep them there is needed to designand implement effective policy and services for this population.